Educating for Tolerance: Multicultural Approaches in Islamic Religious Education - Lestari, Putri Ayu (Sinergi International Journal of Islamic Studies, 2024)
This narrative review explores the integration of multicultural values within Islamic education in public schools, focusing on how inclusive practices contribute to tolerance and social harmony. The study aims to analyze existing literature on the topic and evaluate the effectiveness of pedagogical and institutional strategies. A systematic search was conducted across Scopus, Web of Science, ERIC, and Google Scholar using relevant keywords such as "multicultural Islamic education" and "inclusivity in Islamic education." Studies were selected based on relevance, quality, and empirical depth.  The results highlight four main themes: curriculum integration, the roles of teachers and leadership, effective teaching strategies, and barriers to implementation. Schools that integrate inclusive values into Islamic education foster students' empathy, tolerance, and interfaith understanding. Teachers and school leaders are key facilitators, while project-based learning and interactive media prove effective in promoting multicultural awareness. However, systemic challenges such as policy gaps, limited teacher training, and community resistance persist. Local contexts significantly influence implementation, indicating a need for adaptable and context-sensitive strategies. The findings suggest that strengthening teacher training, aligning national and local policies, and involving community stakeholders are critical for advancing multicultural Islamic education. These insights offer valuable guidance for future research and educational reforms aimed at building inclusive, pluralistic societies through Islamic schooling.